Makna Lirik Lagu Kurung Manuk Dalam Kesenian Gondang Buhun Kampung Adat Kuta Ciamis - Lilis Nurul Fatimah (Paraguna, 2022)
Meaning is the intention to be discussed through a word. Likewise, every song certainly has a meaning and a message in it. This paper focuses on analyzing a song contained in the Gondang Buhun art typical of the Kuta Ciamis Traditional Village. Gondang Buhun art is an art that emerged from the creative ideas of the Kuta people in ancient times which became a necessity for entertainment when pounding rice in the lisung. With this research, it can be an information and reference for the audience regarding the contents of the songs contained in the ancient Buhun songs in the Gondang Buhun art, typical of the Kuta Ciamis Traditional Village, West Java.